Design : a very short introduction. - Heskett, John, ....- (Oxford : University Press, 2005)
John Heskett wants to transform the way we think about design by showing how integral it is to our daily lives, from the spoon we use to eat our breakfast cereal, and the car we drive to work in, to the medical equipment used to save lives. Design combines 'need' and 'desire' in the form of a practical object that can also reflect the user's identity and aspirations through its form and decoration. This concise guide to contemporary design goes beyond style and taste to look at how different cultures and individuals personalize objects. Heskett also reveals how simple objects, such as a toothpick, can have their design modified to suit the specific cultural behaviour in different countries. There are also fascinating insights into how major companies such as Nokia, Ford, and Sony approach design. Finally, the author gives us an exciting vision of what design can offer us in the future, showing in particular how it can humanize new technology.
Keywords: Geschiedenis; Ontwerpen